Gambaran Employee Well-Being Karyawan Layanan Nasabah pada Program Mekaar PT Pemodalan Nasional Madani: Penelitian - Kartika Ratri Walupi; Tarmidi; Ferry Novliadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to describe the level and dimensions of well-being among customer service employees at PT Pemodalan Nasional Madani (PNM) Mekaar in North Sumatra. The three dimensions examined were life well-being, workplace well-being, and psychological well-being. A quantitative approach with a descriptive design was employed. The participants consisted of 277 active employees selected using cluster sampling. Employee well-being was measured using the employee well-being scale developed by Zheng et al. (2015) and adapted into Indonesian. The final scale included 12 items, with each dimension represented by four items. Construct validity was tested through Confirmatory Factor Analysis (CFA), and the reliability coefficient was 0.949. Data analysis was conducted descriptively using Jamovi version 2.7.14. Results showed that most employees fell into the high well-being category. The mean scores of all dimensions were also high, indicating balanced well-being. This balance allows employees to maintain quality of life and positive psychological states. Employees with high well-being can perform tasks effectively and consistently. The findings highlight the importance of maintaining and developing well-being continuously. Sustained well-being contributes to achieving optimal work performance. The results provide practical implications for PNM management. Strategies to strengthen employee well-being are essential for organizational success.